Scientifically Unaccepted Beliefs on Traditional Health Care Using Energy Techniques - Reyhan Kama, A. S.; Rossalina, Lolla; Nugroho, Syaifudin (Lafadz Jaya Publisher, 2024)
Practices that use methods that are not scientifically acceptable, such as psychics and traditional health services, are part of cultures in various parts of the world, tribes, races, and throughout the history of human civilization until now. This research uses a qualitative, phenomenological approach, which is based on the theory of